Who bears the burden of real estate transfer taxes? Evidence from the German housing market - Mathias Dolls; Clemens Fuest; Carla Krolage; Florian Neumeier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
This paper examines the effects of real estate transfer taxes (RETT) on house prices using a rich micro dataset on German properties covering the period from 2005 to 2018. We exploit a 2006 constitutional reform that allowed states to set their own RETT rates, leading to frequent increases in states' tax rates in subsequent years. Our monthly event study estimates indicate a price response that strongly exceeds the change in the tax burden for single transactions. I.e., twelve months after a reform, a one percentage point increase in the tax rate reduces property prices by on average 3.5%. Effects are stronger for apartments and apartment buildings than for singlefamily houses. We interpret these results in the context of a theoretical model that accounts for the effects of RETT on a property's resale value. If a property is expected to be traded more frequently in the future, the decline in its price can exceed the increase in the tax burden. Moreover, larger price effects can be explained by higher bargaining power of sellers.
Keywords: H22; H71; R32; R38; 330; Real estate transfer taxes; property taxes; housing market